Analysis Concept; Continuing Care of Post-Intensive Care Syndrome - Lahati, Nurul Safira; Suhartini, Suhartini; Anggorowati, Anggorowati (International Journal of Nursing and Health Services (IJNHS), 2024)
Background: ICU aftercare is characterized by various physical, emotional, cognitive, and psychosocial symptoms that appear while receiving care in the Intensive Care Unit and continue after discharge and will negatively affect the patient's quality of life. Objective: Analyzing continuing care to refine the definition and analyze what is needed in continuing care after treatment in the ICU. Method:  The article searches used data based on PubMed, Clinical Key, and Science Direct. Walker and Avant's approach was used to guide this concept analysis, which consisted of eight steps, namely concept selection, Continuing care), determining the purpose of the analysis; analyzing Continuing care to refine the definition, and analyze what are the needs in continuing care after treatment in the ICU), identifying all uses of the concept, defining its attributes, identifying antecedents and consequences, identifying model cases, identifying reverse cases and identifying empirical references from defining empirical attributes. Result: Some of the attributes of the concept of continuous care include monitoring and management of post-critical illness symptoms, planning transitions of care from the ICU to the ward, patient education and guidance, and solving problems in overcoming the obstacles faced by post-ICU patients.  Recommendation: Provide standard guidelines or protocols for the continuing care of post-ICU patients. The analysis concept can provide scientific evidence and practice to manage patients with post-ICU care syndrome